Teaching problem-solving and clinical reasoning: 20 years experience with video-supported small-group learning. - Dequeker J; Jaspaert R (Medical Education, 1998)
In the context of a curriculum reform the Faculty of Medicine of the University of Leuven, Belgium, introduced a new teaching project: video-supported small-group learning on problem-solving and clinical reasoning. The aim of this study is to reflect 20 years experience. The video-supported sessions for sixth-year medical students during their practical year in peripheral hospitals were constructed in four stages. The first stage is the video presentation of a case with history-taking and physical examination. The student and three tutors of internal medicine make notes and can ask further questions and perform additional physical examination acts after the video presentation. The coordinator of the course, who knows the patient, then simulates the patient and the doctor to answer the questions. The second stage consists of making up individually a synoptic problem list, integrating history and physical examination; a differential diagnosis list with the most likely diagnosis fitting the problem list; and a list with investigations to be asked for confirming the diagnosis. The third stage consists of three small student groups discussing the three lists requested in stage 2. Each small group of students, passively assisted by a tutor, has to come to the consensus lists. The fourth stage is the confrontation of the consensus lists of the three groups with the aim of coming to an overall agreement. At this stage tutors are more actively involved in the discussion. Several learning processes are involved in this way of teaching. During the first stage the students learn the traditional teaching 'see one, do one and teach one', a demonstration of a full history and physical examination. By asking for additional information they learn by a critical attitude and by developing a strategy of fact-finding. During the second and third stages, by making their lists and during the consensus processes, they learn the significance of individual findings, problem-framing and the synthesis of history and physical examination data in medical concepts. The third and fourth parts of the sessions bring up the process of clinical reasoning, formulation of a working hypothesis, the discussion of the pathophysiology of findings, clustering of problems and epidemiological considerations as incidence and prevalence. Finally, the exercise to select diagnostic tests gives the students the possibility of appreciating the value of sensitivity/specificity and risks, benefits and costs of diagnostic procedures. These video-supported clinical problem-solving and reasoning sessions were positively appraised by students, teachers and medical faculty over the years. Over 20 years, more than 90 cases have been recorded on video, with a widespread variation in diagnoses and clinical presentations. Small-group teaching with the aid of a video case, as described in this paper, can promote enjoyable learning for students and teachers.